2018
DOI: 10.1038/s41524-018-0089-4
|View full text |Cite
|
Sign up to set email alerts
|

Phase-field model of pitting corrosion kinetics in metallic materials

Abstract: Pitting corrosion is one of the most destructive forms of corrosion that can lead to catastrophic failure of structures. This study presents a thermodynamically consistent phase field model for the quantitative prediction of the pitting corrosion kinetics in metallic materials. An order parameter is introduced to represent the local physical state of the metal within a metal-electrolyte system. The free energy of the system is described in terms of its metal ion concentration and the order parameter. Both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 66 publications
(90 reference statements)
4
52
0
1
Order By: Relevance
“…The major drawback of this model is its limitation to 1-D geometry problems, while PF models, in principle, should naturally extend to 2-and 3-D geometries without any changes in the formulation. Ansari et al 20 overcame this problem and proposed a PF model that showed good agreement with the experimental results in both 1-and 2-D cases. They also presented a set of examples to show the ability of their model to capture the effects of complex microstructures.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…The major drawback of this model is its limitation to 1-D geometry problems, while PF models, in principle, should naturally extend to 2-and 3-D geometries without any changes in the formulation. Ansari et al 20 overcame this problem and proposed a PF model that showed good agreement with the experimental results in both 1-and 2-D cases. They also presented a set of examples to show the ability of their model to capture the effects of complex microstructures.…”
Section: Introductionmentioning
confidence: 93%
“…Readers are referred to our previous PF work where the effect of the variation of applied potential is studied in detail including a comparison with the experimental results. 20 In this work, we focus on the evolution of ICP and its role in corrosion kinetics. Now, the 1-D MPF model is used to simulate an ICP phase between the electrolyte and the metal.…”
Section: Electrochemical Reactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…aço inoxidável pode apresentar zonas com tensões residuais, e, há indicações que a corrosão não seja uniforme nessas regiões, resultando em diferentes taxas de corrosão para diferentes direções. Segundo a literatura, zonas com tensão residual compressiva são menos facilmente corroídas do que zonas sem tensão residual, e estas, por sua vez, são menos suscetíveis à corrosão que zonas com tensão residual trativa(ANSARI et al, 2018).O efeito da tensão residual no comportamento de corrosão do aço inoxidável austenítico SUS 316L foi indicado na literatura (TAKAKUWA; SOYAMA, 2015). Corpos de prova foram tratados para se obter diversos acabamentos superficiais, de forma a excluir fatores além da tensão residual, tais como: textura, microdeformações e tamanho de grão, os relação ao meio com pH 7,2.…”
unclassified